Study of the psychoemotional status of patients with medium and severe acne severity on the background of isotretinoin monotherapy (Sotret) - Pavel E. Konnov; Antonina A. Arsenieva; Yuri A. Tokarev (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Rationale. Acne vulgaris is a widespread chronic disease with no age, gender, or race restrictions. It does not pose a direct threat to the patient's life, but is reflected in his psycho-emotional status, which requires appropriate medical intervention. Purpose of the study. To study the psychoemotional status of patients aged 2224 years with moderate and severe acne and its changes during monotherapy with isotretinoin (Sotret). Methods. In an open, non-randomized study lasting 12 months, 310 students of the Samara State Medical University were included (52% healthy, 33% with mild acne, 13% with a moderate degree, 2% with a severe degree). All patients in the study before treatment and after 3, 6, 12 months were assessed the severity of the course using the dermatological index of acne (DIA); quality of life assessment using the Cardiff Acne Disability Index (CADI scale); assessment of the psychological and social impact of acne using the APSEA questionnaire. All patients received monotherapy using the drug Erase. The median and interquartile distance Me (Q3-Q1) were indicated as descriptive statistics. The Wilcoxon signed rank test was used to compare related groups. The comparison was carried out with 95% confidence. Results. An analysis of the assessment of the psychological and social status of patients with moderate and severe acne before treatment, 3, 6, 12 months after the start of treatment with isotretinoin (Erase) is presented. The study included 36 people (20 women and 16 men) aged 22 to 24 years with a disease duration from 1 to 10 years. The results of psychological testing at various intervals gave comparable data: all patients had a pronounced persistent level of social maladjustment. An important indicator of the effectiveness of acne therapy with isotretinoin is the frequency of cases of the formation of a persistent clinical effect from treatment, which is clearly expressed in the restoration of the psycho-emotional background of patients, improving the quality of life of patients. Conclusion. An important indicator of the effectiveness of acne therapy with Erase is the frequency of cases of the formation of a stable clinical effect of treatment, which is clearly expressed in the restoration of the psycho-emotional background of patients, improving the quality of life of patients. The treatment allowed us to change the psychoemotional background of our patients for the better, which increased their motivation to study, communication, and the desire for self-development.